2020
DOI: 10.1371/journal.pone.0231041
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with pneumococcal carriage and density in children and adults in Fiji, using four cross-sectional surveys

Abstract: This study describes predictors of pneumococcal nasopharyngeal carriage and density in Fiji. We used data from four annual (2012-2015) cross-sectional surveys, pre-and postintroduction of ten-valent pneumococcal conjugate vaccine (PCV10) in October 2012. Infants (5-8 weeks), toddlers (12-23 months), children (2-6 years), and their caregivers participated. Pneumococci were detected and quantified using lytA qPCR, with molecular serotyping by microarray. Logistic and quantile regression were used to determine pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 54 publications
0
15
1
Order By: Relevance
“…Pneumococcus became more easily detectable in the presence of rhinovirus infection [38] . In our study we found a negative association between ETS and VT carriage which is in contradiction with other reports [39] . Greenberg et al showed high rates of VT carriage in children exposed to tobacco smoke [40] .…”
Section: Discussioncontrasting
confidence: 99%
“…Pneumococcus became more easily detectable in the presence of rhinovirus infection [38] . In our study we found a negative association between ETS and VT carriage which is in contradiction with other reports [39] . Greenberg et al showed high rates of VT carriage in children exposed to tobacco smoke [40] .…”
Section: Discussioncontrasting
confidence: 99%
“…A possible explanation is that Sp transmission is high in Belgian DCCs, as high density of Sp in the nasopharynx is suggested to be a predictor of both transmission and disease probability ( 53 , 54 ). Dunne et al found that having upper respiratory tract infection symptoms was associated with an increased pneumococcal density ( 55 57 ). In the current study, 36.4% of children in DCCs presented common cold symptoms, which associates with the high pneumococcal density in DCC-children.…”
Section: Discussionmentioning
confidence: 99%
“…high Sp density in the nasopharynx is suggested to be a predictor of transmission probability [50, 51] and of disease. Dunne et al found that having upper respiratory tract infection symptoms was associated with an increased pneumococcal density [5254]. In Belgium, 36.4% of children in DCCs presented common cold symptoms, which associates with the high pneumococcal density in DCC-children.…”
Section: Discussionmentioning
confidence: 99%